Mutação na tríade catalítica da IsPETase: Um estudo com simulações de dinâmica molecular - BRUNO CAMARGO BRAGA (2023)
Plastic waste causes serious environmental problems worldwide, and biological recycling is one of the most eco-friendly methods to deal with it. The discovery of Ideonella sakaiensis PET hydrolase (IsPETase) attracted the interest of the scientific community. Its mesophilic nature is an interesting feature for new perspectives in polyethylene terephthalate (PET) degradation research. Here, we use a Molecular Dynamics approach and discuss the possibility of variations of the canonical catalytic triad at pH 7 and 300 K. We prepare three variants and perform a comparative Molecular Docking protocol of BHET, − bis(2- hydroxyethyl) terephthalate − with these three variants and the wildtype. We performed molecular dynamics simulations focusing on the nucleophilic distance and protonation states of the chosen residues in our mutations. During this work, we noticed the possibility of automating the use of the computational packages AMBER/AMBERtools. A program called ASM.py, from the term AMBER Simulation Manager, was developed for this purpose and registered under the license GNU GPL at the National Institute of Industrial Property (INPI). In all simulations, the ligand remained bound to the active site. The total binding energy in the variants decreased but always remained favorable for interaction. When analyzing the interaction contribution of each residue, the simulations with the wildtype and D206E showed a more stable connection with basically the same energy pattern. However, the variants with lysine showed a reduction in the unfavorable contributions − while the D206E/H237K showed an intermediate behavior when compared to the single mutants. The new charge distribution and side chains conformation for both lysine variants maintained the nucleophilic distance while pushing the ligand away from the oxyanion gap. The one-residue mutants studied here did not show promising results. However, the peculiar behavior of D206E/H237K provokes curiosity about what consequences might arise in empirical data. We believe our discussion may benefit future efforts regarding PET degradation efficiency under environmental conditions.